2007
DOI: 10.1016/j.neuron.2007.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Regions of Monkey Parietal Cortex Process Visual 3D Shape

Abstract: The intraparietal cortex is involved in the control of visually guided actions, like reach-to-grasp movements, which require extracting the 3D shape and position of objects from 2D retinal images. Using fMRI in behaving monkeys, we investigated the role of the intraparietal cortex in processing stereoscopic information for recovering the depth structure and the position in depth of objects. We found that while several areas (CIP, LIP, and AIP on the lateral bank; PIP and MIP on the medial bank) are activated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
151
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(173 citation statements)
references
References 72 publications
(128 reference statements)
18
151
2
Order By: Relevance
“…In a similar vein, the effects we observed in parietal regions were generally weaker than those in earlier visual areas, potentially reflecting the use of stimuli that may not drive these areas optimally. Parietal regions have been reported to respond to more complex disparity-defined stimuli (e.g., slant and curvature) than those used here (Sereno et al, 2002;Tsutsui et al, 2002;Durand et al, 2007). Additionally, it is possible that these higher areas encode information about disparity-defined depth position using a sparser code than other areas, resulting in less biased voxel responses and thereby reducing the performance of the MVPA technique.…”
Section: Classification Of Depth Position For Correlated and Anticorrmentioning
confidence: 95%
“…In a similar vein, the effects we observed in parietal regions were generally weaker than those in earlier visual areas, potentially reflecting the use of stimuli that may not drive these areas optimally. Parietal regions have been reported to respond to more complex disparity-defined stimuli (e.g., slant and curvature) than those used here (Sereno et al, 2002;Tsutsui et al, 2002;Durand et al, 2007). Additionally, it is possible that these higher areas encode information about disparity-defined depth position using a sparser code than other areas, resulting in less biased voxel responses and thereby reducing the performance of the MVPA technique.…”
Section: Classification Of Depth Position For Correlated and Anticorrmentioning
confidence: 95%
“…Since the TEs and AIP neurons are also selective for 2D shape in frontoparallel planes, they carry all the information needed to represent 3D shape from stereo. Using fMRI in the awake monkey we showed that these two regions are sensitive to the interaction between surface order and disparity, responding more to binocular curved 3D surfaces than to binocular flat surfaces at different depths, relative to their respective monocular controls (Durand et al, 2007;Joly et al, 2007). We thus have a MR signature for second-order disparityselective neurons and the aim of the present experiments is to use this signature in human subjects to chart the regions of the human brain that may house similar neurons.…”
Section: Introductionmentioning
confidence: 97%
“…It is worth pointing out that in the monkey we also have an MR signature for first order selective neurons (Durand et al, 2007), but this was not used in the present experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Visual areas in the PPC in humans and monkeys exhibit selectivity for three-dimensional cues of shape such as structurefrom-motion (SFM) (Vanduffel et al, 2002), stereopsis, and perspective (Shikata et al, 1996(Shikata et al, , 2001(Shikata et al, , 2003Sugihara et al, 2002;Anderson and Siegel, 2005;Orban et al, 2006;Durand et al, 2007). Some of the three-dimensional cue-selective neurons in these regions exhibit properties that are suggestive of a role in "high-level" visual perception.…”
Section: Introductionmentioning
confidence: 99%